2021
DOI: 10.1038/s41380-021-01171-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiological risk factors for suicidal thoughts and behaviors in adolescence: a consideration of the role of puberty

Abstract: Suicide is the second leading cause of death among adolescents. While clinicians and researchers have begun to recognize the importance of considering multidimensional factors in understanding risk for suicidal thoughts and behaviors (STBs) during this developmental period, the role of puberty has been largely ignored. In this review, we contend that the hormonal events that occur during puberty have significant effects on the organization and development of brain systems implicated in the regulation of social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 152 publications
0
36
0
Order By: Relevance
“…Possibly, as suggested by Ho and colleagues (Ho et al, 2021), exposure to hormones, in a period of high neural plasticity such as in puberty, leaves an individual more susceptible to the effects of daily life stressors. Future studies should look at pubertal development in relation to daily life stressors to assess whether this can prove detrimental in the development of mental health problems in autistic individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possibly, as suggested by Ho and colleagues (Ho et al, 2021), exposure to hormones, in a period of high neural plasticity such as in puberty, leaves an individual more susceptible to the effects of daily life stressors. Future studies should look at pubertal development in relation to daily life stressors to assess whether this can prove detrimental in the development of mental health problems in autistic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, differential pubertal onset has been reported in ASC (Corbett et al, 2020;Ingudomnukul et al, 2007;Knickmeyer et al, 2006;Pohl et al, 2014;Tordjman et al, 1997). This differential pubertal onset has been linked to a myriad of problems, such as depression and suicidal ideation (Copeland et al, 2019;Ho et al, 2021). Therefore, it is of the utmost importance to examine the effect that pubertal timing has in ASC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that pubertal development parallels changes within neural circuits subserving reward seeking and reward valuation (Ho et al, 2021) -key circuits linked to risk for adolescent internalizing symptoms (Davey et al, 2008;Forbes, 2011;Luking et al, 2016) -we tested whether self-reported, behavioral, or neural signatures of reward sensitivity moderated the association between early pubertal timing and internalizing symptoms. We hypothesized that, across domains, greater reward sensitivity would attenuate the association between early pubertal timing and internalizing symptoms.…”
Section: The Role Of Reward Processes In the Association Between Pubertal Timing And Internalizing Symptomsmentioning
confidence: 99%
“…Similar reward processes may also modulate risk for internalizing symptoms in younger adolescents transitioning to puberty. Notably, hormonal processes initiated early in puberty introduce changes within the aforementioned reward-sensitive circuits (Goddings et al, 2019;Ho et al, 2021;Peper et al, 2013;Piekarski et al, 2017;Wierenga et al, 2018). Pubertal onset may introduce a period in which risk for internalizing symptoms is altered alongside functional changes within these reward processing networks (Nelson et al, 2005;Pfeifer & Allen, 2021).…”
Section: Introductionmentioning
confidence: 99%